Entrepreneurial intention and startup preparation: A study among business students in Malaysia. Issue 6 (18th August 2017) - Mamun, Abdullah Al; Nawi, Noorshella Binti Che; Mohiuddin, Muhammad; Shamsudin, Siti Farhah Fazira Binti; Fazal, Syed Ali
ABSTRACT: Intention, as the starting point of pursuing self-employment and creating new ventures, is crucial before actually establishing a business enterprise. Entrepreneurship is understood to be an essential ingredient for enhancing a country's economic competitiveness, growth, and sustainability while confronting the escalating challenges of globalization, such as increasing unemployment. This study provides empirical evidence on the factors influencing entrepreneurial intention and startup preparations among university students in Malaysia. The findings provide scholars and academic policymakers with insights into the effectiveness of Malaysia's entrepreneurial education as designed and practiced by public universities. The Malaysian government should apply these findings to fortify existing policies and programs and formulate new ones to support graduate entrepreneurs, while universities and other higher education institutions should provide high-quality entrepreneurial courses and programs to young Malaysians to foster an inclination toward entrepreneurship.